Rancang Bangun Aplikasi Halo Cat Berbasis Mobile Dengan Menggunakan Metodologi Scrum Sebagai Alat Konsultasi Online Dokter Hewan - Rahayu, Sri; Kurniadi, Dede; Irfanov, Muhammad (Jurnal Algoritma, 2025)
Owners' lack of knowledge about cat health often leads to cat illnesses not being detected early, even leading to death. About 65% of cats are only found to be sick when brought to the clinic, which is often due to busy owners. This makes the time to consult with a veterinarian unavailable. This research aims to create an Android-based application that can be a link between people who have cats as pets and veterinarians, in consulting related problems experienced by the cat owner. The results showed that Scrum contributed to the development of an efficient Halo Cat application, with accurate time estimation and features that support consultation.